Knowing Microbes, Living Healthier: The Association Between Microbiology Literacy and Health-Promoting Behaviors - Fiskiyatul Jannah; James Gordon James (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to determine the relationship between microbiology literacy and health-promoting behaviors among pre-service biology teachers. It also sought to examine the strength of the association and the contribution of microbiology literacy to students’ health-promoting behaviors. Methodology: A quantitative correlational design was employed. Participants consisted of 60 Biology Education students selected through simple random sampling from a population of 134 students. Data were collected using a microbiology literacy multiple-choice test and a health-promoting behavior questionnaire based on a four-point Likert scale. Instrument validity and reliability were reviewed by experts. Data were analyzed using IBM SPSS Statistics through descriptive statistics, normality testing, linearity testing, Pearson’s Product-Moment correlation, and coefficient of determination analysis. Main Findings: The results revealed a significant positive relationship between microbiology literacy and health-promoting behaviors. The correlation coefficients were r = 0.521 and r = 0.451, indicating moderate positive associations. The significance tests confirmed that the relationships were statistically significant at the 5% level. Microbiology literacy explained 27.14% and 20.34% of the variance in health-promoting behaviors, suggesting that students with higher microbiology literacy tended to demonstrate better health-promoting behaviors. Novelty/Originality of this study: This study extends existing research by specifically examining microbiology literacy rather than general health literacy as a predictor of health-promoting behaviors. It provides empirical evidence on how microbiological knowledge acquired through higher education is associated with students’ daily health practices, contributing to the integration of biology education, health literacy, and behavioral science.